Triggering Receptor Expressed on Myeloid Cell 2 R47H Exacerbates Immune Response in Alzheimer’s Disease Brain - Korvatska, Olena; Kiianitsa, Kostantin; Ratushny, Alexander; Matsushita, Mark; Beeman, Neal; Chien, Wei-Ming; Satoh, Jun-Ichi; Dorschner, Michael O.; Keene, C. Dirk; Bammler, Theo K.; Bird, Thomas D.; Raskind, Wendy H. (Frontiers in Immunology, 2020)
The R47H variant in the microglial TREM2 receptor is a strong risk factor for Alzheimer's disease (AD). To characterize processes affected by R47H we performed integrative network analysis of genes expressed in brains of AD patients with R47H, sporadic AD without the variant and patients with polycystic lipomembranous osteodysplasia with sclerosing leukoencephalopathy (PLOSL), a systemic disease with early onset dementia caused by loss-of function mutations in TREM2 or its adaptor TYROBP. While sporadic AD had few perturbed microglial and immune genes, TREM2 R47H AD demonstrated upregulation of interferon type I response and pro-inflammatory cytokines accompanied by induction of NKG2D stress ligands. In contrast, PLOSL had distinct sets of highly perturbed immune and microglial genes that included inflammatory mediators, immune signaling, cell adhesion and phagocytosis. TREM2 knock-out in THP1, a human myeloid cell line that constitutively expresses the TREM2-TYROBP receptor, inhibited response to the viral RNA mimetic poly(I:C), and overexpression of ectopic TREM2 restored the response. Compared to wild type protein, R47H TREM2 had higher stimulatory effect on the interferon type I response signature. Our findings point to a role of the TREM2 receptor in the control of the interferon type I response in myeloid cells and provide insight regarding the contribution of R47H TREM2 to AD pathology.